2006
DOI: 10.1007/s10658-006-9059-7
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of treatments for the control of the bacterial apical necrosis of mango (Mangifera indica) caused by Pseudomonas syringae pv. syringae

Abstract: Bacterial apical necrosis is a critical disease in the main production area of mango in Europe. It is caused by Pseudomonas syringae pv. syringae, and produces necrotic lesions on mango buds and leaves, causing severe yield losses due to a decrease of flowering and fruit set. A field study to evaluate control treatments against bacterial apical necrosis was carried out during three seasons on mango trees cv. Tommy Atkins in Huelva (Spain). Experimental treatments included Bordeaux mixture, fosetyl-Al, acibenzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…They were assayed to control some bacterial plant diseases like fire blight, citrus canker, apical necrosis of mango, etc. Most of these products do not produce phytotoxicity and their efficacy is sometimes comparable to that of antibiotics or copper-based compounds while others could not control these diseases (Brisset et al, 2000;Cazorla et al, 2006;Graham & Leite, 2004;Scortichini, 2002,). There are reports of acibenzolar-S-methyl-related activation of certain genes involved in defense responses in olive leaves of the cultivar Lechín de Sevilla (Muñoz et al, 2005).…”
Section: Direct Controlmentioning
confidence: 99%
“…They were assayed to control some bacterial plant diseases like fire blight, citrus canker, apical necrosis of mango, etc. Most of these products do not produce phytotoxicity and their efficacy is sometimes comparable to that of antibiotics or copper-based compounds while others could not control these diseases (Brisset et al, 2000;Cazorla et al, 2006;Graham & Leite, 2004;Scortichini, 2002,). There are reports of acibenzolar-S-methyl-related activation of certain genes involved in defense responses in olive leaves of the cultivar Lechín de Sevilla (Muñoz et al, 2005).…”
Section: Direct Controlmentioning
confidence: 99%
“…The benefits of using phosphite (H 2 PO 3 − ), also called phosphonate, to control plant diseases caused by oomycetes have been known since the 1970s and the aluminium salt of the ethyl ester of phosphorous acid (fosetyl‐Al) has been registered as a fungicide under the trade name of Aliette (Guest & Grant, ). Fosetyl‐Al was later evaluated as a bactericide, but was found to induce variable and irregular controls of bacterial diseases (McGuire, ; Chase, ; Sugar et al ., ; Cazorla et al ., ). However, with the European Union's ban on the use of the antibiotic streptomycin in agriculture in 2004 (EUR‐Lex 32004D0129), a need for alternative methods of bacterial disease control was created, and fosetyl‐Al was registered as a bactericide in Belgium and other countries.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, the addition of 0.938 g L −1 fosetyl‐Al to an amino‐acid‐rich agar medium reduced the pH to 3.7 and totally inhibited Pseudomonas syringae growth, although survival tests indicated that P. syringae cells were not killed at that concentration (Moragrega et al ., ); pH 3.7 is below the p K a of the R groups of histidine (6.0), glutamic acid (4.25) and aspartic acid (3.86), and below the limit of pH 4.25–4.5 tolerated by P. syringae for growth (Palleroni, ; Bultreys & Gheysen, ). Fosetyl‐Al can affect the bacterial survival (Chase, ), but 24‐h periods in shaken suspensions containing 4–8 g L −1 fosetyl‐Al were necessary to prevent P. syringae growth on agar medium 72 h after plating (Cazorla et al ., ). The indirect stimulation of plant defences by fosetyl‐Al was also proposed to play a role against bacterial diseases, as already postulated for oomycete diseases, because the acidity could not explain that neutralized fosetyl‐Al was often as efficient as fosetyl‐Al in plant trials (Chase, ).…”
Section: Introductionmentioning
confidence: 97%
“…Although many compounds have been reported to control bacterial diseases in fruit trees, only one study of control methods has been reported in mango crops. This suggested that the most effective treatment for controlling BAN was the spraying of copper compounds Bordeaux mixture (BM) (Cazorla et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It forms a thick film on plant surfaces due to the calcium it contains (Becerra, 1995). BM actively controls BAN, but no effect has been observed on P. syringae levels, suggesting that antimicrobial activity may not be its main mode of action against BAN (Cazorla et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%